2005
DOI: 10.1117/12.584943
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric changes to KH 2 PO 4 during laser-induced breakdown

Abstract: The local structure of KH 2 PO 4 crystals (so-called KDP) at laser-induced damage sites created by irradiation with ∼ 3-ns, 355-nm laser pulses is studied by a combination of Raman scattering and photoluminescence spectroscopies. We compare spectra from pristine material, surface and bulk laser-induced damage sites, as well as from KPO 3 references. Results show that irradiation with fluences above the laser-induced breakdown threshold leads to stoichiometric changes at surface damage sites but not at bulk dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…We have not unambiguously identified the origin of this new line. It is close to a series of Raman features found in a study 6 of stoichiometric changes in KDP accompanying surface damage caused by laser-induced breakdown. These features were attributed to KPO 3 vibrations.…”
Section: Modified Materials Surrounds Bulk Damage Sitesupporting
confidence: 84%
“…We have not unambiguously identified the origin of this new line. It is close to a series of Raman features found in a study 6 of stoichiometric changes in KDP accompanying surface damage caused by laser-induced breakdown. These features were attributed to KPO 3 vibrations.…”
Section: Modified Materials Surrounds Bulk Damage Sitesupporting
confidence: 84%
“…For the KH 2 PO 4 + Mg(OH) 2 system (data not shown), two endothermic peaks at 240 and 400 °C for the sample mixture before milling correspond to the decomposition of KH 2 PO 4 (240 °C) and Mg(OH) 2 (400 °C), both releasing moles of water. It is known that KH 2 PO 4 undergoes dissociation at around 240 °C, , and analysis of the solids by XRD after KH 2 PO 4 had been heated at 240 °C showed that KH 2 PO 4 decomposed to KPO 3 . It has also been reported in the literature that Mg(OH) 2 decomposes at around 400 °C. For the sample mixture milled at 100 rpm, the intensity of the endothermic peak positions characteristic of KH 2 PO 4 and Mg(OH) 2 decreased, and these peaks disappeared from the sample mixtures milled at mill rotational speeds of 300−600 rpm; however, new endothermic peaks appeared at around 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…For the KH 2 PO 4 + Mg(OH) 2 system (data not shown), two endothermic peaks at 240 and 400 °C for the sample mixture before milling correspond to the decomposition of KH 2 PO 4 (240 °C) and Mg(OH) 2 (400 °C), both releasing moles of water. It is known that KH 2 PO 4 undergoes dissociation at around 240 °C, 19,20 and analysis of the solids by XRD after KH 2 PO 4 had been heated at 240 °C showed that KH 2 PO 4 decomposed to KPO 3 . It has also been reported in the literature that Mg(OH) 2 decomposes at around 400 °C.…”
Section: Mechanochemical (Mc) Synthesis Of Kmgpo 4 Andmentioning
confidence: 99%
“…In reality, most crystals contain complex cluster defects formed by a mixture of various intrinsic defects, 19 making it hard to evaluate the influence of each intrinsic defect on damage intuitively. 5,20–22 Therefore, studying the effects of intrinsic defects on laser damage in crystals one by one, and then analyzing their comprehensive effects, is an effective way to study crystal damage and provide solid theoretical support for crystal damage research. Liu and Wang et al 23–25 investigated the reaction mechanism of point defects such as H and O using ab initio calculations based on density-functional theory (DFT) and analyzed the effect of the existence of point defects on the optical properties of crystals.…”
Section: Introductionmentioning
confidence: 99%